Influência do sistema de preparo e manejo de um latossolo vermelho nas suas propriedades físico-hídricas - de Medeiros, Gerson Araújo (2009)
The intensive use of the land for agricultural propose causes a series of modifications in attributes, which can take to soil degradation. In this context, the main goal of this research was to evaluate the influence of the soil tillage systems and management on its physical and hydric characteristics. The evaluations were carried out in July of 1999, at experimental plots of a Latossolo vermelho, a clay oxisoil, in the Faculdade de Engenharia Agrícola of the UNICAMP, at the county of Campinas, state of São Paulo. These plots were managed with the following treatments, along a period of eight years: no-tillage, chisel ploughing, conventional system with disk ploughing and revolving hoe. The evaluated physical and hydric parameters of the soil were: soil bulk density, particle density, total porosity, macro-porosity, micro-porosity, soil-water retention curve, hydraulic conductivity and basic infiltration. Significant differences were observed between the treatments on soil bulk density, infiltration, total porosity, macro-porosity and the micro-porosity. The chisel ploughing and no-tillage systems presented the higher values of soil bulk density; nevertheless in these conservationist systems were observed the higher values of basic infiltration.